Unraveling Vocabulary Ambiguity: Contextual Lexis Learning and Vocabulary Retention for ESP Learners - Haque, Md.Nurul; Bin Abdul Jabar, Mohd Azidan; Redzuan Abdullah, Muhammad Alif (Forum for Linguistic Studies, 2025)
Ambiguity of meaning exists in every language and at all levels of linguistic structure. A common feature of English for Specific Purposes (ESP) texts is the ambiguity of meaning in the teaching and learning of ESP. Vocabulary retention is another problematic issue for learners at all levels in every language. For ESP students, Contextual Lexis Learning (CLL) is beneficial, since it has a decisive impact on establishing meaning and retaining vocabulary. The current study aims to investigate the effectiveness of CLL in helping ESP students understand the meaning of vocabulary and retain it. The study involved 50 undergraduate students enrolled in an engineering program, who were assigned to either the experimental group or the control group. Before the training, a pre-test was conducted to determine their levels of proficiency. Post-tests were performed under different conditions after every two training sessions. The results of the T-test and Independent Samples T-test indicate that CLL has a significant and wide-ranging effect on students’ ability to comprehend and produce vocabulary in various situations, as well as to retain it in both the short and long term. The current study demonstrates that CLL methods enhance students’ confidence and autonomy, reducing their reliance on dictionaries and external resources. This article has some curriculum design and pedagogical implications, suggesting that if we equip our students with improved vocabulary proficiency and a greater understanding of language, we must make CLL a component of any ESP program.